Periodická řešení neautonomní Duffingovy rovnice - Zamir, Qazi Hamid (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2020)
Ordinary differential equations of various types appear in the mathematical modelling in mechanics. Differential equations obtained are usually rather complicated nonlinear equations. However, using suitable approximations of nonlinearities, one can derive simple equations that are either well known or can be studied analytically. An example of such "approximative" equation is the so-called Duffing equation. Hence, the question on the existence of a periodic solution to the Duffing equation is closely related to the existence of periodic vibrations of the corresponding nonlinear oscillator.

Ordinary differential equations of various types appear in the mathematical modeling in mechanics. Differential equations obtained are usually rather complicated nonlinear equations. However, using suitable approximations of nonlinearities, one can derive simple equations that are either well known or can be studied analytically. An example of such "approximative" equation is the so-called Duffing equation. Hence, the question on the existence of a periodic solution to the Duffing equation is closely related to the existence of periodic vibrations of the corresponding nonlinear oscillator.
Periodic solutions to nonautonmous Duffing equation
Keywords: Differential equation; Duffing equation; periodic solution; existence; uniqueness.; Differential equation; Duffing equation; periodic solution; existence; uniqueness.